Ecomorphological Differentiation of Feeding Structures within the Antarctic Fish Species Flock Trematominae (Notothenioidei) from Terra Nova Bay (Ross Sea) - Erica Carlig; Davide Di Blasi; Eva Pisano; Marino Vacchi; Gianfranco Santovito; Laura Ghigliotti (Journal of Marine Science and Engineering, 2022)
The Antarctic endemic fish genus Trematomus (Trematominae, Notothenioidei) includes 15 species very diverse in morphology, lifestyle and feeding ecology. Co-occurring on the continental shelf, they occupy different habitats and a wide range of ecological niches as the result of adaptive radiation during their evolutionary history. Ecomorphological differentiation is a key feature of adaptive radiations, with a general trend for specialization following divergence. Here, we investigated the trophic adaptive morphology and ecology of six Trematomus species from Terra Nova Bay (Ross Sea) through feeding apparatus metrics and geometric morphometrics. The suction index (SI), the mechanical advantage in jaw closing (MA), the relative surface of the adductor mandibulae muscle and nine morphological traits related to feeding structures were analysed. Head shape clearly differentiates the benthic (T. bernacchii, T. hansoni and T. pennellii) from the pelagic (T. eulepidotus and T. borchgrevinki) species. The position of the eyes and the orientation of the mouth also contribute to specific morphological differences and specialization. Interestingly, T. newnesi stands at an intermediate position and the mouth is clearly oriented upwards compared to the other congeneric species.